BINA KAMPUNG MANDIRI PROGRAM SADAR KESEHATAN MASYARAKAT DAN SADAR HUKUM WARGA KAMPUNG BUTI - Adi Sumarsono; Mulyadi A. Tajuddin; Dina Fitri Septarini (Musamus Devotion Journal, 2023)
The people of Buti village, who are in the Samkai palace, are one of the people living around the Musamus University campus. The existence of a community that is dominated by residents who make a living as fishermen because the area around the residence is in the area around the coast. The majority of the population, who are Indigenous Papuans, prioritize tolerance and togetherness. During the Covid 19 pandemic, which was felt by everyone, residents in Kampung Buti needed information that was valid and could touch every level of society. The focus of this service is in the health and legal fields. The method of this service activity is in the form of counseling, mentoring and application. The implementation of this activity increases the knowledge and skills of the community in creating independent campers who understand and know the health sector and are aware of the rule of law in society. The partners involved are members of the Kampung Buti community. The implementation of community service activities is carried out by complying with health protocols. The result of this activity is the creation of an independent village in which the community understands and is skilled in two fields, namely the health sector, especially implementing health protocols and increasing knowledge in law. As for each improvement from the two fields, the Partner community can feel it in the form of awareness in maintaining personal health, maintaining environmental health and obeying not violating applicable laws